Spectroscopic and Microscopic Characterization of Volcanic Ash from Puyehue-(Chile) Eruption: Preliminary Approach for the Application in the Arsenic Removal - Botto, Irma Lía (2013)
Volcanic ash fromPuyehueCordonCaulleVolcanicComplex (Chile), emitted on June 4, 2011, and deposited inVilla LaAngostura at ∼40 kmof the source, was collected and analyzed by Raman spectroscopy, optical and scanning electron microscopy (SEM-EDS), Xray diffraction (XRD), surface area (BET), and chemical analysis (ICP-AES-MS technique).Themineralogical and physicochemical study revealed that the pyroclastic mixture contains iron oxides in the form of magnetite and hematite as well as pyroxene and plagioclase mineral species and amorphous pumiceous shards. Carbonaceous material was also identified. Physicochemical techniques allow us to select two representative samples (average composition and Fe-rich materials) which were used to analyze their performances in the adsorption process to remove arsenic from water. Additional iron activation by means of ferric salts was performed under original sample. Results showed that the low-cost feedstock exhibited a good adsorption capacity to remove the contaminant, depending on the iron content and the water pH.